2022
DOI: 10.1523/eneuro.0124-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Diurnal Variation and Sex Differences in Hippocampal Neurophysiology and Spatial Memory

Abstract: Circadian rhythms are biological processes that cycle across 24 h and regulate many facets of neurophysiology, including learning and memory. Circadian variation in spatial memory task performance is well documented; however, the effect of sex across circadian time (CT) remains unclear. Additionally, little is known regarding the impact of time-of-day on hippocampal neuronal physiology. Here, we investigated the influence of both sex and time-of-day on hippocampal neurophysiology and memory in mice. Performanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Prior studies that evaluated the regulation of circadian genes by components of the MAPK pathway (e.g., Akashi et al., 2008; Eckel‐Mahan et al., 2008; reviewed by Wang et al., 2020) also showed that their activity peaked in certain brain regions during the day (inactive period for the mice evaluated; Eckel‐Mahan et al., 2008). Moreover, since this disruption of p‐ERK oscillations was linked to an impaired memory persistence (Eckel‐Mahan et al., 2008), the 24‐h modulation of p‐ERK/t‐ERK observed in association with FADD fluctuations might be key for normal physiological activities (e.g., Gaspar et al., 2019; Goode et al., 2022; McCauley et al., 2020; Patke et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies that evaluated the regulation of circadian genes by components of the MAPK pathway (e.g., Akashi et al., 2008; Eckel‐Mahan et al., 2008; reviewed by Wang et al., 2020) also showed that their activity peaked in certain brain regions during the day (inactive period for the mice evaluated; Eckel‐Mahan et al., 2008). Moreover, since this disruption of p‐ERK oscillations was linked to an impaired memory persistence (Eckel‐Mahan et al., 2008), the 24‐h modulation of p‐ERK/t‐ERK observed in association with FADD fluctuations might be key for normal physiological activities (e.g., Gaspar et al., 2019; Goode et al., 2022; McCauley et al., 2020; Patke et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies performed in nocturnal rodents show that hippocampal LTP is remarkably affected by the time of the day and that this modulation stands even after rearing the animals in darkness for a few days, thus demonstrating the dependency on the intrinsic circadian clock rather than on the light cycle. Surprisingly, there is no complete agreement on the direction of the effect: while several studies indicate that hippocampal LTP measured in CA1 is stronger at night, during the active phase of nocturnal animals ( Chaudhury et al, 2005 ; Bowden et al, 2012 ; Nakatsuka and Natsume, 2014 ; Besing et al, 2017 ; Davis et al, 2020 ; Goode et al, 2022 ), other studies provide a different picture, with the peak of LTP during the day ( Raghavan et al, 1999 ; McCauley et al, 2020 ). These differences underline the complexity of the problem of linking circadian rhythm with models of synaptic plasticity and behavioral assays.…”
Section: Circadian Clock Synaptic Plasticity and Cortical Excitabilitymentioning
confidence: 93%
“…(C) mTOR is the converging point between the environmental stimuli and the autonomous circadian clock. Goode et al, 2022), other studies provide a different picture, with the peak of LTP during the day (Raghavan et al, 1999;McCauley et al, 2020). These differences underline the complexity of the problem of linking circadian rhythm with models of synaptic plasticity and behavioral assays.…”
Section: Circadian Clock Synaptic Plasticity and Cortical Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Third, cognitive function includes not only the abilities of learning and memory but also attention, behavioral flexibility, problem-solving, and action planning 88 and hence should not be disregarded. A fourth limitation concerns the diurnal variations and sex differences in hippocampal physiology and behavior 89…”
Section: Hippocampal Lfs Alleviates Deficits In Long-term Memory Recallmentioning
confidence: 99%